PENINGKATAN KINERJA PADA PROSES PRODUKSI KERIPIK PARU DAN UNTHUK YUYU - Hera Sisca Prasmita; Jhauharotul Muchlisyiyah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2017)
Beef lungs chips and unthuk yuyu are local snack from Kanigoro, Blitar, East Java. Beef lungs chips is made of beef lungs that boiled and stored in freezer. Frozen beef lungs is cut into pieces, dipped in spices, coated in flour and then fried in oil until golden. Unthuk yuyu is local snack made of glutinous rice flour, eggs, sugar and coconut milk. The process of making unthuk yuyu are all ingredients are mixed and then molded using cake mold that specific for unthuk yuyu, and the last is fried this molded dough until golden. The problems of producing beef lungs chips are the low capacity of frying beef lungs and still using conventional knife to cut the beef lungs. The problems of producing untruk yuyu are butter mixing still use small mixer, sugar grinding and coconut shreding still using traditional implementation and need more labour.. There are several solution to overcome those problems by introduce the new advance technology in food processing After introduction of meat slicer and high pressure stove in beef lungs chips processing can increase the efficiency and capacity of cutting frozen beef lungs four times higher and increase of frying capacity two times higher than before. By introducing of grinding meachine, shreding meachine and planetary mixer also can increase the efficiency and capacity of producing untruk yuyu. By using planetary mixer 15 L in size, the capacity of mixing process could be increase.